2019
DOI: 10.3390/md17020121
|View full text |Cite
|
Sign up to set email alerts
|

9-Methylfascaplysin Is a More Potent Aβ Aggregation Inhibitor than the Marine-Derived Alkaloid, Fascaplysin, and Produces Nanomolar Neuroprotective Effects in SH-SY5Y Cells

Abstract: β-Amyloid (Aβ) is regarded as an important pathogenic target for Alzheimer’s disease (AD), the most prevalent neurodegenerative disease. Aβ can assemble into oligomers and fibrils, and produce neurotoxicity. Therefore, Aβ aggregation inhibitors may have anti-AD therapeutic efficacies. It was found, here, that the marine-derived alkaloid, fascaplysin, inhibits Aβ fibrillization in vitro. Moreover, the new analogue, 9-methylfascaplysin, was designed and synthesized from 5-methyltryptamine. Interestingly, 9-methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 52 publications
0
29
0
Order By: Relevance
“…One of the most powerful marine-derived compounds that produce in vitro neuroprotective effects is the 9-methylfascaplysin. In the research of Sun et al [ 133 ], fascaplysin was used for designing 9-methylfascaplysin to improve its activity. Fascaplysin ( Figure 7 ) is a extensively active benzoyl-linked β-carboline alkaloid initially extracted from the Fijian sponge Fascaplysinopsis ; this molecule showed antitumoral and antioxidative effects [ 134 ].…”
Section: Marine Drugs In Alzheimer’s Diseasementioning
confidence: 99%
“…One of the most powerful marine-derived compounds that produce in vitro neuroprotective effects is the 9-methylfascaplysin. In the research of Sun et al [ 133 ], fascaplysin was used for designing 9-methylfascaplysin to improve its activity. Fascaplysin ( Figure 7 ) is a extensively active benzoyl-linked β-carboline alkaloid initially extracted from the Fijian sponge Fascaplysinopsis ; this molecule showed antitumoral and antioxidative effects [ 134 ].…”
Section: Marine Drugs In Alzheimer’s Diseasementioning
confidence: 99%
“…Aβ oligomer preparation was described in previous studies reported by us [27][28][29]. Brie y, Aβ peptide was dissolved in hexa uoroisopropanol (HFIP, Aladdin, Shanghai, China) to form Aβ monomers.…”
Section: Preparation Of Aβ Oligomersmentioning
confidence: 99%
“…Based on molecular modeling studies, 9-methylfascaplysin ( Figure 5 g), a fascaplysin derivative, was synthesized [ 60 , 61 ]. Docking analyses suggested that the binding to AChE active site differs from fascaplysin, which only binds to the peripheral anionic site.…”
Section: Marine Natural Productsmentioning
confidence: 99%
“…9-Methylfascaplysin and Aβ possibly interact through hydrogen bonding and hydrophobic interactions, including π-π interactions. It is thought that the direct interaction between this fascaplysin derivative and Aβ causes competition between the intramolecular bonds of Aβ aggregates leading to the inhibition of Aβ self-assembly [ 61 ]. Studies performed in vitro also showed its potential to activate antioxidant enzymes and thus, to produce neuroprotective effects against ROS.…”
Section: Marine Natural Productsmentioning
confidence: 99%